EP357 Transarterial embolisation for the treatment of acute gynecological cancer bleeding. (1st November 2019) - Meyer-Wilmes, P; Powerski, M; Fischbach, F; Damm, R; Omari, J; Pech, M
Abstract : Introduction/Background: Acute bleeding in patients with gynecological cancer may result in serious life-threatening complications. In these situations, immediate diagnostic and appropriate treatment is a challenge for attending physicians. Accordingly, transarterial embolisation (TAE) has been described as an increasing and effective treatment alternative to surgery and radiotherapy. Methodology: In the present retrospective study 25 patients were included who underwent a TAE in the period from January 2006 to June 2013 due to acute gynecological cancer bleeding. The objective of this study was to assess the efficiency and outcome of TAE. Results: Cervical cancer was the most common cause of gynecological bleeding (19/25, 76.0%). The primary technical success rate was 92.0% (n=23). 21 patients were analysed in the 30-day follow-up. The clinical success rate was achieved in 90.5% (n=19). A clinical failure due to rebleeding was observed in 9.5% (n=2). No associations were revealed between rebleeding and technical/clinical factors. Within 30 days after the last TAE the complication and mortality rates were 0.0% and 5.0% (n=1), respectively. Conclusion: TAE was found as an effective and safe treatment in the clinical setting of acute gynecological cancer bleeding. An important component of efficient management is an early and interdisciplinary care. Optimal treatment can only be achieved by close cooperation between gynecologists, radiotherapists and interventional radiologists. Further randomised trials are needed to obtain more evidence, especially in predictive factors. Disclosure: Nothing to disclose.